Level of Emotional Balance among Students with Learning Disabilities and its Relationship to Self-Acceptance - Ahmad Mohammad Melhem; Tahani Bassam Al-Shamayleh (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: This study aims to identify the level of emotional balance of students with LD and its relationship to self-acceptance. Methods: In order to achieve the objectives of the study, a descriptive cor-relational approach was used. The sample of the study consisted of (125) male and female students with LD, who were selected in a convenient way from third and fourth grades from Al-Kasbah schools in Karak governorate, Jordan. Two measures of the levels of emotional balance and self-acceptance were developed, and their validity and reliability were verified. Results: The study finds that the level of emotional balance and self-acceptance of students with LD came at an average level. The results show that there were no statistically significant differences at the level (α≤0.05) in the level of emotional balance among students with LD due to gender. They reveal a statistically significant difference at the level of (α≤0.05) in the level of self-acceptance of students with LD due to gender in favor of fe-males. Moreover, there is a correlation between the level of emotional bal-ance and self-acceptance of students with LD. Conclusions: The study recommends working on training teachers in coping skills in order to help students with LD disabilities have emotional balance and self-acceptance.